An Unexpected Interaction between Sofosbuvir/Ledipasvir and Atorvastatin and Colchicine Causing Rhabdomyolysis in a Patient with Impaired Renal Function. (22nd August 2016) - Patel, Shyam; Andres, Jennifer; Qureshi, Kamran
Abstract : Hepatitis C virus (HCV) infection affects roughly 170 million people worldwide. Sofosbuvir/Ledipasvir (Sof/Led) is a new once daily direct acting antiviral combination pill that was approved in October 2014 for use in patients with HCV genotype 1 infection. Coadministration of Sof/Led is studied only with rosuvastatin which shows significantly increased level of drug and is associated with increased risk of myopathy, including rhabdomyolysis. There is no mention of such HMG-CoA reductase inhibitor interaction as a class, as pravastatin did not have any clinically significant interaction with Sof/Led. Other myotoxic drugs, including colchicine are not studied. We present a case of a serious drug interaction between Sof/Led and atorvastatin, in the background of CKD and colchicine use.